A completion fluid and method of making the same
Patent Information
- Application Number
- CN202211710037.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-12-29
AI Technical Summary
此外,测试油管等管柱在失效的旧泥浆中配伍性也会存在较大问题,引发试油管柱被埋
[0052]与现有技术相比,该疏水缔合聚合物Poly-Q、改性用聚合物Poly-G可应用于完井工作液中其有益效果包括:
Smart Images

Figure SMS_3 
Figure SMS_13 
Figure SMS_23
Abstract
Description
Technical Field
[0001] This invention relates to the field of petroleum exploration and development technology, specifically to the field of oil and gas field drilling and completion technology, and particularly to a completion fluid and its preparation method in the field of oil and gas field exploration and development technology. Background Technology
[0002] Currently, most well completion and testing fluids used are recycled drilling mud. This refers to drilling fluid that has been circulated through the wellbore for several weeks during the drilling process and then returned to the well. Due to the influence of geothermal temperature and the high-speed shearing at the nozzles, joints, and interfaces of drilling tools such as drill bits and drill pipes after circulating for several weeks at the bottom of the well, this type of drilling fluid has poor suspension capacity.
[0003] Because these drilling fluids contain weighting materials, such as barite, they possess a certain density. However, to meet the different density requirements of completion fluids, additional weighting materials are needed. For example, barite, low- or high-priced inorganic salts, and organic salts can be used to re-weight the old drilling mud.
[0004] However, due to factors such as the prolonged well testing and completion process and the increase in formation temperature, the residual treatment agents in the weighted old mud deteriorate more rapidly at high temperatures, causing barite-based weighting materials and small suspended rock cuttings in the old mud to settle. This results in the barite and other weighting materials losing their original weighting effect, leading to a decrease in density. Small particles settle onto the completion string or in the annulus between the completion string and casing, causing the completion string to become stuck. Furthermore, the reintroduction of inorganic or organic salts as weighting materials into the old mud further degrades the polymeric treatment agents in the old mud, also leading to the settling of barite-based weighting materials and small suspended rock cuttings in the old mud.
[0005] The settling of barite-based weighting materials and small rock fragments suspended in old drilling mud can cause well-testing tubing and tools to become stuck or jammed in this type of old drilling mud. Furthermore, the compatibility of testing tubing and other tubing in ineffective old drilling mud can be problematic, leading to the tubing becoming buried. This severely impacts the progress of well completion and testing.
[0006] The problem of old mud corroding the test tubing and test tools is also a thorny issue that hinders well testing and completion operations.
[0007] Therefore, it is necessary to develop a new type of well completion fluid. This fluid should be able to prevent the settling of weighting materials, maintain the suspension of weighting materials such as barite inserted into the well, and meet the construction requirements for well completion fluids with high density requirements. Summary of the Invention
[0008] The first aspect of the present invention is to provide a hydrophobic associative polymer Poly-Q and a method for preparing the same.
[0009] Therefore, the technical solution of the present invention is as follows:
[0010] A hydrophobic associative polymer Poly-Q is characterized in that it is prepared by polymerization reaction of monomers A, B, C, D and E.
[0011] in,
[0012] The chemical structure of monomer A is as follows: Where n = 1 to 5
[0013] The chemical structure of monomer B is as follows: Where R1 is
[0014] The chemical structure of monomer C is as follows:
[0015] The chemical structural formula of monomer D is:
[0016] The chemical structural formula of monomer E is:
[0017] The ratio of monomers A, B, C, D, and E is (0.2–1):(0.3–1):(0.5–1):(0.2–1):(0.3–1).
[0018] Preferably, the hydrophobic associative polymer Poly-Q has a weight-average molecular weight of 1500–2000 g / mol.
[0019] Preferably, the molecular weight distribution coefficient of the hydrophobic associating polymer Poly-Q is 1.1 to 1.3;
[0020] A method for preparing the above-mentioned hydrophobic associating polymer Poly-Q includes the following specific steps:
[0021] S1. Emulsifier, alkali metal carbonate and / or alkali metal bicarbonate and water are stirred at a high speed of 500-600 r / min for 20-30 min to obtain emulsifier mixture;
[0022] The ratio of the amount of emulsifier, the amount of alkali metal carbonate and / or alkali metal bicarbonate to the volume of water is (0.4-0.6):(0.2-0.5):100.
[0023] S2. Add monomers A, B, C, D and E in a molar ratio of (0.2-1):(0.3-1):(0.5-1):(0.2-1):(0.3-1) to the emulsifier mixture dropwise. During this process, inert gas is introduced at a rate of 0.3-0.5 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300-400 r / min until the mixture is homogeneous.
[0024] The ratio of the total amount of substance of monomers A, B, C, D and E to the volume of water in step S1 is (3-5):100.
[0025] S3. Transfer the emulsion reaction mixture obtained in step S2 to a reaction vessel and introduce inert gas at a rate of 0.3 to 0.5 L / min for protection. Under a stirring speed of 200 to 300 r / min, heat the emulsion to 45 to 50°C at a heating rate of 1°C / min and keep it at that temperature for 5 to 8 minutes. Then add 1 / 4 to 1 / 3 of the weight of initiator.
[0026] Continue stirring at a speed of 200–300 r / min, and introduce inert gas at a rate of 0.3–0.5 L / min while stirring for 15–20 min. Then, heat the emulsion to 55–60 °C at a rate of 1 °C / min and hold it at that temperature for 5–8 min. Finally, add the remaining weight of initiator.
[0027] Stir at a speed of 200-300 r / min, and introduce inert gas at a rate of 0.3-0.5 L / min and stir for 15-20 min. Then, heat to 70 °C at a heating rate of 1 °C / min, stop introducing inert gas, close the reaction vessel, and keep the reaction at this temperature for 8 h.
[0028] S4. Cool the mixed product obtained in step S3 to 40-45°C, add alkali metal carbonate or alkali metal bicarbonate to adjust its pH value to neutral, and further cool to 25-30°C. After washing with anhydrous ethanol and drying, the hydrophobic associative polymer Poly-Q is obtained.
[0029] Another object of the present invention is to provide a well completion fluid containing the above-mentioned hydrophobic associating polymer Poly-Q.
[0030] To increase the density of the completion fluid and maintain its stable density properties.
[0031] Therefore, the present invention provides a modified barite as a weighting material for the well completion fluid.
[0032] Therefore, the present invention provides the following technical solution:
[0033] Barite was grafted and modified using a modifying polymer, Poly-G, and the resulting product is the modified barite described in this invention. The modifying polymer Poly-G contains monomers F, G, H, and K, as shown below.
[0034] in,
[0035] The chemical structure of monomer F is as follows:
[0036] The chemical structure of monomer G is as follows:
[0037] The chemical structure of monomer H is as follows:
[0038] The chemical structure of monomer K is as follows:
[0039] The molar ratio of monomers F, G, H and K is (0:3~1):(0.5~1):(0.5~1):(0.2~1); the weight-average molecular weight of the modified polymer Poly-G is 1000~2000g / mol.
[0040] Preferably, the molecular weight distribution of the modified polymer Poly-G is 1.1 to 1.3;
[0041] The specific steps for preparing the modified polymer Poly-G are as follows:
[0042] Step 1: Mix the emulsifier and water at a high speed of 600-800 r / min for 20-30 minutes to obtain an emulsifier mixture;
[0043] The ratio of the amount of emulsifier to the volume of water is (0.6–0.8):100.
[0044] Step 2: Add monomers F, G, H and K in a molar ratio of (0:3~1):(0.5~1):(0.5~1):(0.2~1) dropwise to the emulsifier mixture. During this process, inert gas is introduced at a rate of 0.6~0.8L / min for protection, and a shear emulsification stirrer is used to stir the emulsion at a shear rate of 500~600r / min until it is uniformly mixed.
[0045] The ratio of the total amount of substance of monomers F, G, H and K to the volume of water in Step 1 is (5-8):100.
[0046] Step 3: Transfer the emulsion obtained in Step 2 to a reaction vessel and introduce inert gas at a rate of 0.6-0.8 L / min. Under stirring speed of 350-500 r / min, heat the emulsion to 50-60℃ at a heating rate of 1℃ / min and hold it at that temperature for 5-8 min. Then add 1 / 4-1 / 3 of the weight of initiator.
[0047] Continue stirring at a speed of 350–500 r / min, and introduce inert gas at a rate of 0.6–0.8 L / min and stir for 15–20 min. Then, heat the emulsion to 65–70 °C at a heating rate of 1 °C / min and hold it at that temperature for 5–8 min. Finally, add the remaining weight of initiator.
[0048] Continue stirring at a speed of 350–500 r / min and introduce inert gas at a rate of 0.6–0.8 L / min for 15–20 min. Then, heat the emulsion to 75 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop introducing inert gas, close the reaction vessel, and keep the reaction at that temperature for 4 h.
[0049] Stop the reaction and continue stirring at a rate of 200 r / min. After the reaction liquid cools down naturally to 30-35℃, reduce the stirring speed to 100 r / min and continue cooling to room temperature (25±2℃). Stop stirring to obtain an emulsion containing the modified polymer Poly-G.
[0050] The ratio of the amount of initiator to the volume of water in step S1 is 0.06 to 0.08:100; wherein the initiator is potassium persulfate or ammonium persulfate.
[0051] Step 4: The emulsion obtained in Step 3 is washed and dried with anhydrous ethanol at room temperature. The resulting solid is the modified polymer Poly-G.
[0052] Compared with existing technologies, the hydrophobic associating polymer Poly-Q and the modified polymer Poly-G can be applied to well completion fluids, and their beneficial effects include:
[0053] (1) The hydrophobic associative polymer Poly-Q forms a liquid with a certain viscosity through intermolecular association, interlocking and cross-linking of molecular chains, which can effectively increase the viscosity and shear force of the well completion fluid. It is beneficial for suspension, such as for weighting materials, rock fragments in the formation, sand and other particulate materials;
[0054] (2) The hydrophobic associating polymer Poly-Q can be directly added to the prepared well completion fluid. Alternatively, the solid product obtained by evaporating the emulsion at 25–30°C can be used for fluid preparation.
[0055] (3) During the pumping process, the hydrophobic associative polymer Poly-Q has excellent recoverable deformation characteristics and forms a variable three-dimensional network structure due to the interlacing, crossing and entanglement of molecular chains in the physical space of the well completion working fluid, which can reduce the pumping friction.
[0056] (4) The quaternary ammonium salt structure contained in the hydrophobic associating polymer Poly-Q can degrade into surfactants containing quaternary ammonium salt structures after the hydrophobic associating polymer molecules break or break down. This helps the completion fluid to mix with the oil phase in the formation and form an emulsion.
[0057] (5) The quaternary ammonium salt structure and sulfonate structure in the hydrophobic associative polymer Poly-Q emulsify the crude oil seeping from the formation, reduce the surface tension and viscosity of the oil phase, and help dilute and extract crude oil in the near-wellbore zone.
[0058] (6) Compared with existing technologies, this completion fluid uses modified barite as a weighting material. On the one hand, it can increase the viscosity of the completion fluid through interactions with the hydrophobic associating polymer Poly-Q, such as electrostatic attraction, intermolecular interleaving, cross-linking and entanglement.
[0059] On the other hand, due to the presence of the modified polymer Poly-G on the surface of the modified barite, the modified barite is better suspended in the completion fluid and less prone to settling. This helps to better maintain the density of the completion fluid.
[0060] (7) The modified polymer Poly-G contains quaternary ammonium salt structure and carboxylate structure, which can also form an emulsion with the crude oil seeping from the formation, reducing the surface tension and viscosity of the oil phase, which is beneficial to the dilution of crude oil in the near-wellbore zone, reducing the flow resistance of crude oil, and helping to extract crude oil.
[0061] (8) When the completion fluid is pumped and squeezed into the formation, the modified barite particles also enter the formation. With the subsequent pumping of fluid, the modified barite is embedded in the formation pores or microfractures, reducing the filtration loss of the completion fluid.
[0062] (9) The completion fluid has a stable and high density, which can ensure the needs of the completion work.
[0063] (10) The working fluid has a simple formula and is easy to operate on site. Detailed Implementation
[0064] The present invention will be further described below with reference to specific embodiments, but the following embodiments are by no means intended to limit the present invention. Unless otherwise defined, the technical terms used in the following embodiments have the same meaning as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0065] In the following embodiments, the shear emulsifying stirrer used was a JRJ300-I type shear emulsifying stirrer manufactured by Shanghai Yueci Electronic Technology Co., Ltd.; when characterizing the hydrophobic associating polymers prepared in the following embodiments, their weight-average molecular weight was measured using GPC gel chromatography (the experimental instrument was a gel chromatograph from Wyatt Medical Systems, USA, model DAWNHELEOSII); their molecular weight distribution index was the ratio of the weight-average molecular weight to the number-average molecular weight obtained by GPC gel chromatography.
[0066] In the context of this invention, the endpoints of the disclosed ranges and any values are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values; for numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as a specific advantage in the context of this invention.
[0067] The first aspect of this invention aims to provide a well completion fluid. This well completion fluid is a mixture formed by a hydrophobic associative polymer Poly-Q and a modified barite in a certain proportion with water.
[0068] The second aspect of the present invention aims to provide the hydrophobic associative polymer Poly-Q and its preparation method.
[0069] Therefore, the technical solution of the present invention is as follows:
[0070] A hydrophobic associative polymer Poly-Q is characterized in that it is prepared by polymerization reaction of monomers A, B, C, D and E.
[0071] in,
[0072] The chemical structure of monomer A is as follows: Where n = 1 to 5
[0073] The chemical structure of monomer B is as follows: Where R1 is
[0074] The chemical structure of monomer C is as follows:
[0075] The chemical structural formula of monomer D is:
[0076] The chemical structural formula of monomer E is:
[0077] The ratio of monomers A, B, C, D, and E is (0.2–1):(0.3–1):(0.5–1):(0.2–1):(0.3–1).
[0078] Preferably, the polymer has a weight-average molecular weight of 1500–2000 g / mol.
[0079] Preferably, the hydrophobic associative polymer Poly-Q has a molecular weight distribution of 1.1 to 1.3;
[0080] A method for preparing the above-mentioned hydrophobic associating polymer Poly-Q includes the following specific steps:
[0081] S1. Emulsifier, alkali metal carbonate and / or alkali metal bicarbonate and water are stirred at a high speed of 500-600 r / min for 20-30 min to obtain emulsifier mixture;
[0082] The ratio of the amount of emulsifier, the amount of alkali metal carbonate and / or alkali metal bicarbonate to the volume of water is (0.4-0.6):(0.2-0.5):100.
[0083] S2. Add monomers A, B, C, D and E in a molar ratio of (0.2-1):(0.3-1):(0.5-1):(0.2-1):(0.3-1) to the emulsifier mixture dropwise. During this process, inert gas is introduced at a rate of 0.3-0.5 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300-400 r / min until the mixture is homogeneous.
[0084] The ratio of the total amount of substance of monomers A, B, C, D and E to the volume of water in step S1 is (3-5):100.
[0085] S3. Transfer the emulsion reaction mixture obtained in step S2 to a reaction vessel and introduce inert gas at a rate of 0.3 to 0.5 L / min for protection. Under a stirring speed of 200 to 300 r / min, heat the emulsion to 45 to 50°C at a heating rate of 1°C / min and keep it at that temperature for 5 to 8 minutes. Then add 1 / 4 to 1 / 3 of the weight of initiator.
[0086] Continue stirring at a speed of 200–300 r / min, and introduce inert gas at a rate of 0.3–0.5 L / min while stirring for 15–20 min. Then, heat the emulsion to 55–60 °C at a rate of 1 °C / min and hold it at that temperature for 5–8 min. Finally, add the remaining weight of initiator.
[0087] Stir at a speed of 200-300 r / min, and introduce inert gas at a rate of 0.3-0.5 L / min and stir for 15-20 min. Then, heat to 70 °C at a heating rate of 1 °C / min, stop introducing inert gas, close the reaction vessel, and keep the reaction at this temperature for 8 h.
[0088] S4. Cool the mixed product obtained in step S3 to 40-45°C, add alkali metal carbonate or alkali metal bicarbonate to adjust its pH value to neutral, and further cool to 25-30°C. After washing with anhydrous ethanol and drying, the hydrophobic associative polymer Poly-Q is obtained.
[0089] Compared with existing technologies, the hydrophobic associating polymer Poly-Q and the modified polymer Poly-G can be applied to well completion fluids, and their beneficial effects include:
[0090] (1) The hydrophobic associative polymer Poly-Q forms a liquid with a certain viscosity through intermolecular association, interlocking and cross-linking of molecular chains, which can effectively increase the viscosity and shear force of the well completion fluid. It is beneficial for suspension, such as for weighting materials, rock fragments in the formation, sand and other particulate materials;
[0091] (2) The hydrophobic associating polymer Poly-Q can be directly added to the prepared well completion fluid. Alternatively, the solid product obtained by evaporating the emulsion at 25–30°C can be used for fluid preparation.
[0092] (3) During the pumping process, the hydrophobic associative polymer Poly-Q has excellent recoverable deformation characteristics and forms a variable three-dimensional network structure due to the interlacing, crossing and entanglement of molecular chains in the physical space of the well completion working fluid, which can reduce the pumping friction.
[0093] (4) The quaternary ammonium salt structure contained in the hydrophobic associating polymer Poly-Q molecule can degrade into a surfactant containing a quaternary ammonium salt structure after the hydrophobic associating polymer Poly-Q molecule breaks or is destroyed. This helps the completion fluid to mix with the oil phase in the formation and form an emulsion.
[0094] (5) The quaternary ammonium salt structure and sulfonate structure in the hydrophobic associative polymer Poly-Q molecule can emulsify the formation and seep crude oil after the hydrophobic associative polymer Poly-Q molecule breaks or is destroyed, reducing the surface tension and viscosity of the oil phase, which helps to dilute and extract crude oil in the near-wellbore zone.
[0095] (6) Compared with existing technologies, this completion fluid uses modified barite as a weighting material. On the one hand, it can increase the viscosity of the completion fluid through interactions with the hydrophobic associating polymer Poly-Q, such as electrostatic attraction, intermolecular interleaving, cross-linking and entanglement.
[0096] On the other hand, due to the presence of the modified polymer Poly-G on the surface of the modified barite, the modified barite is better suspended in the completion fluid and less prone to settling. This helps to better maintain the density of the completion fluid.
[0097] (7) The modified polymer Poly-G contains quaternary ammonium salt structure and carboxylate structure. When the modified polymer Poly-G molecules break or are destroyed, they can also form an emulsion with the crude oil seeping from the formation, which reduces the surface tension and viscosity of the oil phase, which is beneficial to the dilution of crude oil in the near-wellbore zone, reduces the flow resistance of crude oil, and helps the extraction of crude oil.
[0098] (8) When the completion fluid is pumped and squeezed into the formation, the modified barite particles also enter the formation. With the subsequent pumping of fluid, the modified barite is embedded in the formation pores or microfractures, reducing the filtration loss of the completion fluid.
[0099] (9) The completion fluid has a stable and high density, which can ensure the needs of the completion work.
[0100] (10) The working fluid has a simple formula and is easy to operate on site.
[0101] A third aspect of the present invention is to provide a modified polymer Poly-G and a modified barite thereof.
[0102] Therefore, the present invention provides the following technical solution:
[0103] Barite was grafted and modified using a polymer called Poly-G. The copolymer Poly contains monomers F, G, H, and K, as shown in the following formula.
[0104] in,
[0105] Monomer F is
[0106] Monomer G is Monomer H is Monomer K is
[0107] The molar ratio of monomers F, G, H and K is (0:3~1):(0.5~1):(0.5~1):(0.2~1); the weight-average molecular weight of the modified polymer Poly-G is 1000~2000g / mol.
[0108] Preferably, the molecular weight distribution of the modified polymer Poly-G is 1.1 to 1.3;
[0109] The specific steps for preparing the modified polymer Poly-G are as follows:
[0110] Step 1: Mix the emulsifier and water at a high speed of 600-800 r / min for 20-30 minutes to obtain an emulsifier mixture;
[0111] The ratio of the amount of emulsifier to the volume of water is (0.6–0.8):100.
[0112] Step 2: Add monomers F, G, H and K in a molar ratio of (0:3~1):(0.5~1):(0.5~1):(0.2~1) dropwise to the emulsifier mixture. During this process, inert gas is introduced at a rate of 0.6~0.8L / min for protection, and a shear emulsification stirrer is used to stir the emulsion at a shear rate of 500~600r / min until it is uniformly mixed.
[0113] The ratio of the total amount of substance of monomers F, G, H and K to the volume of water in Step 1 is (5-8):100.
[0114] Step 3: Transfer the emulsion obtained in Step 2 to a reaction vessel and introduce inert gas at a rate of 0.6-0.8 L / min. Under stirring speed of 350-500 r / min, heat the emulsion to 50-60℃ at a heating rate of 1℃ / min and hold it at that temperature for 5-8 min. Then add 1 / 4-1 / 3 of the weight of initiator.
[0115] Continue stirring at a speed of 350–500 r / min, and introduce inert gas at a rate of 0.6–0.8 L / min and stir for 15–20 min. Then, heat the emulsion to 65–70 °C at a heating rate of 1 °C / min and hold it at that temperature for 5–8 min. Finally, add the remaining weight of initiator.
[0116] Continue stirring at a speed of 350–500 r / min and introduce inert gas at a rate of 0.6–0.8 L / min for 15–20 min. Then, heat the emulsion to 75 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop introducing inert gas, close the reaction vessel, and keep the reaction at that temperature for 4 h.
[0117] Stop the reaction and continue stirring at a rate of 200 r / min. After the reaction liquid cools down naturally to 30-35℃, reduce the stirring speed to 100 r / min and continue cooling to room temperature (25±2℃). Stop stirring to obtain an emulsion containing the modified polymer Poly-G.
[0118] The ratio of the amount of initiator to the volume of water in step S1 is 0.06 to 0.08:100; wherein the initiator is potassium persulfate or ammonium persulfate.
[0119] Step 4: The emulsion obtained in Step 3 is washed and dried with anhydrous ethanol at room temperature. The resulting solid is the modified polymer Poly-G.
[0120] In this invention, unless otherwise specified, when referring to dosage, the dosage of the modified barite weighting material is based on dry weight.
[0121] Unless otherwise specified, the room temperature of the present invention is 25±2℃.
[0122] In this invention, there are no particular restrictions on the preparation and formulation methods of liquids such as well completion working fluids. Preparation methods well known to those skilled in the art can be used, and will not be elaborated here. Furthermore, the specific operations listed in the following text should not be construed as limitations on this invention.
[0123] The weight-average molecular weight of the copolymers prepared in this invention was measured using a DAWNHELEOS II gel chromatograph from Wyatt Industries, Inc.
[0124] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as the specific disclosure herein.
[0125] The present invention will be described in detail below through examples. Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.
[0126] Example 1
[0127] A hydrophobic associative polymer, Poly-Q, is prepared by the following method:
[0128] S1. Add 1 mol sodium dodecyl sulfonate, 1 mol sodium carbonate and 1 mol OS-15 to 500 mL distilled water and stir at high speed (500 r / min ~ 550 r / min) for 30 min to obtain an emulsifier mixture;
[0129] S2. Add monomers A, B, C, D, and E dropwise to the emulsifier mixture over 15 minutes in the following molar ratio of 0.2:0.3:0.5:0.2:0.3. During this time, purge with nitrogen at a rate of 0.3 L / min and stir the emulsion at a shear rate of 300 r / min using a shear emulsifier until the mixture is homogeneous.
[0130] in,
[0131] The chemical structure of monomer A is as follows: Where n = 1
[0132] The chemical structure of monomer B is as follows: Where R1 is
[0133] The chemical structure of monomer C is as follows:
[0134] The chemical structural formula of monomer D is:
[0135] The chemical structural formula of monomer E is:
[0136] In step S2, the ratio of the total amount of reacting monomers to the volume of water in step S1 is 3:100.
[0137] S3. Transfer the emulsion obtained in step S2 to a reaction vessel and purge with nitrogen at a rate of 0.3 L / min. Heat the emulsion to 45°C at a stirring speed of 300 r / min and a heating rate of 1°C / min and keep it at that temperature. After keeping it at that temperature for 5 min, add 1 / 4 of the weight of potassium persulfate.
[0138] Continue stirring at 300 r / min and introduce nitrogen gas at a rate of 0.3 L / min for 15 min. Then, heat the emulsion to 55 °C at a rate of 1 °C / min and hold it at that temperature for 5 min. After holding at that temperature, add the remaining potassium persulfate.
[0139] Continue stirring at 300 r / min and nitrogen gas is introduced at a rate of 0.3 L / min for 15 min. Then, heat the emulsion to 70 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop the nitrogen gas introduction, close the reaction vessel, and keep the reaction at that temperature for 8 h.
[0140] The reaction was stopped, and the reaction product was allowed to cool naturally to 45°C. Na2CO3 was added to adjust the pH to 7, and the mixture was cooled to 30°C. Stirring was then stopped to obtain an emulsion containing the hydrophobic associative polymer Poly-Q.
[0141] In step S3, potassium persulfate is dissolved in water to prepare a solution, which is then added to the reactor. Specifically, the ratio of the amount of potassium persulfate to the volume of water is 0.03:100.
[0142] S4. The solid obtained after washing and drying the emulsion obtained in step S3 is the hydrophobic associative polymer Poly-Q.
[0143] To accurately characterize the properties of the hydrophobic associating polymer Poly-Q, the polymer was washed with anhydrous ethanol and then dried.
[0144] Testing revealed that the hydrophobic associative polymer Poly-Q prepared in Example 1 had a weight-average molecular weight of 1500 g / mol and a molecular weight distribution coefficient of 1.2. Furthermore, infrared spectroscopy showed that the molecular weight distribution coefficient (MBC) was within the range of 3100–3000 cm⁻¹. -1 1695~1630cm -1 The absence of characteristic peaks indicates the absence of carbon-carbon double bonds, suggesting that monomers A, B, C, D, and E formed a polymer through polymerization. (1270–1010 cm⁻¹) -1 The presence of a special peak for ether indicates that the polymer contains the structure of monomer A.
[0145] 1360~1020cm -1 The presence of characteristic amine peaks indicates the presence of monomer B in the polymer, with peaks in the range of 1725–1705 cm⁻¹. -1 1650~1550cm -1 1350~1020cm -1 The presence of characteristic peaks for amines and ketones indicates that the polymer contains monomeric carbon structures, in the range of 860–800 cm⁻¹. -1 The presence of characteristic peaks indicates that the polymer contains monomer D, with peaks in the range of 810–750 cm⁻¹. -1 The presence of a characteristic peak indicates that the polymer contains monomer E.
[0146] Example 2
[0147] A hydrophobic associative polymer, Poly-Q, is prepared by the following method:
[0148] S1. Add 1.2 mol sodium dodecyl diphenyl ether disulfonate, 1 mol sodium carbonate and 1.3 mol polysorbate-85 to 500 mL distilled water and stir at high speed (500 r / min to 550 r / min) for 30 min to obtain an emulsifier mixture;
[0149] S2. Add monomers A, B, C, D, and E dropwise to the emulsifier mixture over 15 minutes in the following molar ratio of 0.5:0.5:0.7:0.5:0.7. During this time, purge with nitrogen at a rate of 0.3 L / min and stir the emulsion at a shear rate of 300 r / min using a shear emulsifier until the mixture is homogeneous.
[0150] in,
[0151] The chemical structure of monomer A is as follows: Where n = 3
[0152] The chemical structure of monomer B is as follows: Where R1 is
[0153] The chemical structure of monomer C is as follows:
[0154] The chemical structural formula of monomer D is:
[0155] The chemical structural formula of monomer E is:
[0156] In step S2, the ratio of the total amount of reacting monomers to the volume of water in step S1 is 4:100.
[0157] S3. Transfer the emulsion obtained in step S2 to a reaction vessel and purge with nitrogen at a rate of 0.3 L / min. Heat the emulsion to 45°C at a stirring speed of 300 r / min and a heating rate of 1°C / min and keep it at that temperature. After keeping it at that temperature for 5 min, add 1 / 4 of the weight of potassium persulfate.
[0158] Continue stirring at 300 r / min and introduce nitrogen gas at a rate of 0.3 L / min for 15 min. Then, heat the emulsion to 57°C at a heating rate of 1°C / min and keep it at that temperature for 5 min. After that, add the remaining 3 / 4 of the weight of potassium persulfate.
[0159] Continue stirring at 300 r / min and nitrogen gas is introduced at a rate of 0.3 L / min for 15 min. Then, heat the emulsion to 70 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop the nitrogen gas introduction, close the reaction vessel, and keep the reaction at that temperature for 8 h.
[0160] Stop the reaction and allow the reaction product to cool naturally to 45°C. Then, add Na2CO3 to adjust the pH to 7. Continue cooling to 30°C and stop stirring to obtain an emulsion containing hydrophobic associative polymers.
[0161] In step S3, potassium persulfate is dissolved in water to prepare a solution, which is then added to the reactor. Specifically, the ratio of the amount of potassium persulfate to the volume of water is 0.04:100.
[0162] S4. The solid obtained after washing and drying the emulsion obtained in step S3 is the hydrophobic associative polymer Poly-Q.
[0163] To accurately characterize the properties of the hydrophobic associating polymer, the polymer was purified by washing with anhydrous ethanol and then dried.
[0164] Testing revealed that the hydrophobic associative polymer Poly-Q prepared in Example 2 had a weight-average molecular weight of 1700 g / mol and a molecular weight distribution coefficient of 1.3. Furthermore, infrared spectroscopy showed that the molecular weight distribution coefficient was [missing information - likely related to molecular weight distribution]. -1 1695~1630cm -1 The absence of characteristic peaks indicates the absence of carbon-carbon double bonds, suggesting that monomers A, B, C, D, and E formed a polymer through polymerization. (1270–1010 cm⁻¹) -1 The presence of a specific peak for ether indicates the presence of monomer A in the polymer, located between 1360 and 1020 cm⁻¹. -1 The presence of characteristic amine peaks indicates the presence of monomer B in the polymer, with peaks in the range of 1725–1705 cm⁻¹. -1 1650~1550cm -1 1350~1020cm -1 The presence of characteristic peaks for amines and ketones indicates that the polymer contains monomeric carbon structures, in the range of 860–800 cm⁻¹. -1 The presence of characteristic peaks indicates that the polymer contains monomer D, with peaks in the range of 810–750 cm⁻¹. -1 The presence of a characteristic peak indicates that the polymer contains monomer E.
[0165] Example 3
[0166] A hydrophobic associative polymer, Poly-Q, is prepared by the following method:
[0167] S1. Add 1.5 mol sodium dodecyl sulfonate, 1 mol sodium carbonate and 1.5 mol Span 60 to 500 mL distilled water and stir at high speed (500 r / min ~ 550 r / min) for 30 min to obtain an emulsifier mixture;
[0168] S2. Add monomers A, B, C, D and E dropwise to the emulsifier mixture in the following molar ratio of 1:1:1:1:1 over 15 min. During this time, nitrogen gas is introduced at a rate of 0.3 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300 r / min until the mixture is homogeneous.
[0169] in,
[0170] The chemical structure of monomer A is as follows: Where n = 5
[0171] The chemical structure of monomer B is as follows: Where R1 is
[0172] The chemical structure of monomer C is as follows:
[0173] The chemical structural formula of monomer D is:
[0174] The chemical structural formula of monomer E is:
[0175] In step S2, the ratio of the total amount of reacting monomers to the volume of water in step S1 is 5:100.
[0176] S3. Transfer the emulsion obtained in step S2 to a reaction vessel and purge with nitrogen at a rate of 0.3 L / min. Heat the emulsion to 50°C at a stirring speed of 300 r / min and a heating rate of 1°C / min and keep it at that temperature. After keeping it at that temperature for 5 min, add 1 / 4 of the weight of potassium persulfate.
[0177] Continue stirring at 300 r / min and introduce nitrogen gas at a rate of 0.3 L / min for 15 min. Then, heat the emulsion to 60°C at a rate of 1°C / min and keep it at that temperature for 5 min. Then, add the remaining 3 / 4 of the weight of potassium persulfate.
[0178] Continue stirring at 300 r / min and nitrogen gas is introduced at a rate of 0.3 L / min for 15 min. Then, heat the emulsion to 70 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop the nitrogen gas introduction, close the reaction vessel, and keep the reaction at that temperature for 8 h.
[0179] Stop the reaction and allow the reaction product to cool naturally to 45°C. Then, add Na2CO3 to adjust the pH to 7. Continue cooling to 30°C and stop stirring to obtain an emulsion containing hydrophobic associative polymers.
[0180] In step S3, potassium persulfate is dissolved in water to prepare a solution, which is then added to the reactor. Specifically, the ratio of the amount of potassium persulfate to the volume of water is 0.05:100.
[0181] S4. The solid obtained after washing and drying the emulsion obtained in step S3 is the hydrophobic associative polymer Poly-Q.
[0182] To accurately characterize the properties of the hydrophobic associating polymer, the polymer was purified by washing with anhydrous ethanol and then dried.
[0183] The hydrophobic associative polymer Poly-Q prepared in Example 3 was tested and found to have a weight-average molecular weight of [value missing].
[0184] 2000 g / mol, with a molecular weight distribution coefficient of 1.1; additionally, according to infrared spectroscopy, 3100–3000 cm⁻¹ -1 1695~1630cm -1 The absence of characteristic peaks indicates the absence of carbon-carbon double bonds, suggesting that monomers A, B, C, D, and E formed a polymer through polymerization. (1270–1010 cm⁻¹) -1 The presence of a special peak for ether indicates that the polymer contains the structure of monomer A.
[0185] 1360~1020cm -1 The presence of characteristic amine peaks indicates the presence of monomer B in the polymer, with peaks in the range of 1725–1705 cm⁻¹. -1 1650~1550cm -1 1350~1020cm -1 The presence of characteristic peaks for amines and ketones indicates that the polymer contains monomeric carbon structures, in the range of 860–800 cm⁻¹. -1 The presence of characteristic peaks indicates that the polymer contains monomer D, with peaks in the range of 810–750 cm⁻¹. -1 The presence of a characteristic peak indicates that the polymer contains monomer E.
[0186] Example 4
[0187] A modified polymer, Poly-G, is prepared by the following method:
[0188] S1. Add 1.5 mol sodium tetradecyl sulfate and 1.5 mol OP-4 to 500 mL of distilled water and stir at high speed (500 r / min ~ 550 r / min) for 30 min to obtain an emulsifier mixture;
[0189] S2. Add monomers F, G, H and K dropwise to the emulsifier mixture in the following molar ratio of 0:3:0.5:0.5:0.2 over 15 min. During this time, nitrogen gas is introduced at a rate of 0.6 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300 r / min until the mixture is homogeneous.
[0190] The ratio of the total amount of substance of monomers F, G, H and K to the volume of water in Step 1 is 5:100.
[0191] in,
[0192] Monomer F is Monomer G is
[0193] Monomer H is Monomer K is
[0194] S3. Transfer the emulsion obtained in step S2 to a reaction vessel and purge with nitrogen at a rate of 0.6 L / min. Heat the emulsion to 50°C at a stirring speed of 350 r / min and a heating rate of 1°C / min and keep it at that temperature. After keeping it at that temperature for 5 min, add 1 / 4 of the weight of potassium persulfate.
[0195] Continue stirring at 350 r / min and introduce nitrogen gas at a rate of 0.6 L / min for 15 min. Then, heat the emulsion to 65°C at a rate of 1°C / min and hold it at that temperature for 5 min. Finally, add the remaining 3 / 4 of the weight of potassium persulfate.
[0196] Continue stirring at 350 r / min and nitrogen gas is introduced at a rate of 0.6 L / min for 15 min. Then, heat the emulsion to 75 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop the nitrogen gas introduction, close the reaction vessel, and keep the reaction at that temperature for 4 h.
[0197] The reaction was stopped, and the mixture was stirred at a rate of 200 r / min. After the reaction product cooled naturally to 35°C, the stirring speed was reduced to 100 r / min and the mixture was stirred at a rate of 100 r / min. After cooling to 27°C, the stirring was stopped to obtain an emulsion containing hydrophobic associative polymers.
[0198] In step S3, potassium persulfate is dissolved in water to prepare a solution, which is then added to the reactor. Specifically, the ratio of the amount of potassium persulfate to the volume of water is 0.06:100.
[0199] S4. The solid obtained after washing and drying the emulsion obtained in step S3 is the modified polymer Poly-G.
[0200] To accurately characterize the properties of the hydrophobic associating polymer, the polymer was purified by ethanol washing and then dried.
[0201] Testing revealed that the modified polymer Poly-G prepared in Example 4 had a weight-average molecular weight of 1000 g / mol and a molecular weight distribution coefficient of 1.2. Furthermore, infrared spectroscopy showed that the molecular weight distribution coefficient was [missing information - likely related to molecular weight distribution]. -1 1695~1630cm -1 The absence of characteristic peaks indicates the absence of carbon-carbon double bonds, suggesting that monomers F, G, H, and K formed a polymer through polymerization. (885–860 cm⁻¹) -1 The presence of a specific peak for benzene indicates that the polymer contains the monomer F, located in the range of 1360–1020 cm⁻¹. -1 The presence of characteristic amine peaks indicates the presence of monomer G in the polymer, in the range of 1725–1700 cm⁻¹. -1 The presence of characteristic peaks for carboxylic acids indicates that the polymer contains the monomeric hydrogen (H) structure, located at 1680–1630 cm⁻¹. -1 1420~1400cm -1 The presence of amide characteristic peaks indicates that the polymer contains monomer K.
[0202] Example 5
[0203] A modified polymer, Poly-G, is prepared by the following method:
[0204] S1. Add 2.2 mol sodium decyl sulfate and 1.3 mol OP-50 to 500 mL of distilled water and stir at high speed (500 r / min ~ 550 r / min) for 30 min to obtain an emulsifier mixture;
[0205] S2. Add monomers F, G, H and K dropwise to the emulsifier mixture in the following molar ratio of 0.6:0.7:0.7:0.8 over 15 minutes. During this time, nitrogen gas is introduced at a rate of 0.3 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300 r / min until the mixture is homogeneous.
[0206] The ratio of the total amount of substance of monomers F, G, H and K to the volume of water in Step 1 is 6:100.
[0207] in,
[0208] Monomer F is Monomer G is Monomer H is Monomer K is
[0209] S3. Transfer the emulsion obtained in step S2 to a reaction vessel and purge with nitrogen at a rate of 0.6 L / min. Heat the emulsion to 50°C at a stirring speed of 350 r / min and a heating rate of 1°C / min and keep it at that temperature. After keeping it at that temperature for 5 min, add 1 / 4 of the weight of potassium persulfate.
[0210] Continue stirring at 350 r / min and introduce nitrogen gas at a rate of 0.6 L / min for 15 min. Then, heat the emulsion to 65°C at a rate of 1°C / min and hold it at that temperature for 5 min. Finally, add the remaining 3 / 4 of the weight of potassium persulfate.
[0211] Continue stirring at 350 r / min and nitrogen gas is introduced at a rate of 0.6 L / min for 15 min. Then, heat the emulsion to 75 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop the nitrogen gas introduction, close the reaction vessel, and keep the reaction at that temperature for 4 h.
[0212] The reaction was stopped, and the mixture was stirred at a rate of 200 r / min. After the reaction product cooled naturally to 35°C, the stirring speed was reduced to 100 r / min and the mixture was stirred at a rate of 100 r / min. After cooling to 27°C, the stirring was stopped to obtain an emulsion containing hydrophobic associative polymers.
[0213] In step S3, potassium persulfate is dissolved in water to prepare a solution, which is then added to the reactor. Specifically, the ratio of the amount of potassium persulfate to the volume of water is 0.07:100.
[0214] S4. The solid obtained after washing and drying the emulsion obtained in step S3 is the modified polymer Poly-G.
[0215] To accurately characterize the properties of the hydrophobic associating polymer, the polymer was purified by ethanol washing and then dried.
[0216] Testing revealed that the modified polymer Poly-G prepared in Example 5 had a weight-average molecular weight of 1500 g / mol and a molecular weight distribution coefficient of 1.3. Furthermore, infrared spectroscopy showed that the molecular weight distribution coefficient was [missing information - likely related to molecular weight distribution].-1 1695~1630cm -1 The absence of characteristic peaks indicates the absence of carbon-carbon double bonds, suggesting that monomers F, G, H, and K formed a polymer through polymerization. (885–860 cm⁻¹) -1 The presence of a specific peak for benzene indicates that the polymer contains the monomer F, located in the range of 1360–1020 cm⁻¹. -1 The presence of characteristic amine peaks indicates the presence of monomer G in the polymer, in the range of 1725–1700 cm⁻¹. -1 The presence of characteristic peaks for carboxylic acids indicates that the polymer contains the monomeric hydrogen (H) structure, located at 1680–1630 cm⁻¹. -1 1420~1400cm -1 The presence of amide characteristic peaks indicates that the polymer contains monomer K.
[0217] Example 6
[0218] A modified polymer, Poly-G, is prepared by the following method:
[0219] S1. Add 2 mol sodium tetradecyl sulfate and 2 mol OP-4 to 500 mL of distilled water and stir at high speed (500 r / min ~ 550 r / min) for 30 min to obtain an emulsifier mixture;
[0220] S2. Add monomers F, G, H and K dropwise to the emulsifier mixture in a molar ratio of 1:1:1:1 over 15 min. During this time, nitrogen gas is introduced at a rate of 0.3 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300 r / min until the mixture is homogeneous.
[0221] The ratio of the total amount of substance of monomers F, G, H and K to the volume of water in Step 1 is 8:100.
[0222] in,
[0223] Monomer F is Monomer G is Monomer H is Monomer K is
[0224] S3. Transfer the emulsion obtained in step S2 to a reaction vessel and purge with nitrogen at a rate of 0.6 L / min. Heat the emulsion to 50°C at a stirring speed of 350 r / min and a heating rate of 1°C / min and keep it at that temperature. After keeping it at that temperature for 5 min, add 1 / 4 of the weight of potassium persulfate.
[0225] Continue stirring at 350 r / min and introduce nitrogen gas at a rate of 0.6 L / min for 15 min. Then, heat the emulsion to 65°C at a rate of 1°C / min and hold it at that temperature for 5 min. Finally, add the remaining 3 / 4 of the weight of potassium persulfate.
[0226] Continue stirring at 350 r / min and nitrogen gas is introduced at a rate of 0.6 L / min for 15 min. Then, heat the emulsion to 75 °C at a heating rate of 1 °C / min and keep it at that temperature. Stop the nitrogen gas introduction, close the reaction vessel, and keep the reaction at that temperature for 4 h.
[0227] The reaction was stopped, and the mixture was stirred at a rate of 200 r / min. After the reaction product cooled naturally to 35°C, the stirring speed was reduced to 100 r / min and the mixture was stirred at a rate of 100 r / min. After cooling to 27°C, the stirring was stopped to obtain an emulsion containing hydrophobic associative polymers.
[0228] In step S3, potassium persulfate is dissolved in water to prepare a solution, which is then added to the reactor. Specifically, the ratio of the amount of potassium persulfate to the volume of water is 0.08:100.
[0229] S4. The solid obtained after washing and drying the emulsion obtained in step S3 is the modified polymer Poly-G.
[0230] To accurately characterize the properties of the hydrophobic associative polymer, the modified polymer Poly-G was purified by ethanol washing and then dried.
[0231] Testing revealed that the modified polymer Poly-G prepared in Example 6 had a weight-average molecular weight of 2000 g / mol and a molecular weight distribution coefficient of 1.1. Furthermore, infrared spectroscopy showed that the molecular weight distribution coefficient was [missing information - likely related to molecular weight distribution]. -1 1695~1630cm -1 The absence of characteristic peaks indicates the absence of carbon-carbon double bonds, suggesting that monomers F, G, H, and K formed a polymer through polymerization. (885–860 cm⁻¹) -1 The presence of a specific peak for benzene indicates that the polymer contains the monomer F, located in the range of 1360–1020 cm⁻¹. -1 The presence of characteristic amine peaks indicates the presence of monomer G in the polymer, in the range of 1725–1700 cm⁻¹. -1 The presence of characteristic peaks for carboxylic acids indicates that the polymer contains the monomeric hydrogen (H) structure, located at 1680–1630 cm⁻¹. -1 1420~1400cm -1 The presence of amide characteristic peaks indicates that the polymer contains monomer K.
[0232] Test Example 1
[0233] The hydrophobic associating polymer Poly-Q prepared in Example 3 was added at a rate of 25 wt.% and the barite modified by the modified polymer Poly-G prepared in Example 6 was added at a rate of 25 wt.%, and the mixture was thoroughly mixed with deionized water to form a mixture labeled 1. The hydrophobic associating polymer Poly-Q prepared in Example 3 was added at a rate of 35 wt.% and the barite modified by the modified polymer Poly-G prepared in Example 6 was added at a rate of 25 wt.%, and the mixture was thoroughly mixed with deionized water to form a mixture labeled 2. Both mixtures were placed in constant temperature water baths at room temperature and 90°C, respectively. Whether the solutions separated into layers or settled was observed. The experimental results are shown in Tables 1 and 2.
[0234] Table 1. Stratification and Settlement Experiment Data (Ambient Temperature 27℃)
[0235]
[0236]
[0237] As shown in Table 1, at room temperature (27℃), neither mixture No. 1 nor mixture No. 2 showed stratification after 72 hours. Mixture No. 1, however, showed stratification after 96 hours; when the time was further extended to 120 hours, mixture No. 1 exhibited obvious stratification and partial precipitation. Mixture No. 2, on the other hand, showed stratification after 120 hours.
[0238] This phenomenon occurs because the amount of the hydrophobic associating polymer Poly-Q prepared in Example 3 was different in mixtures numbered 1 and 2. Therefore, it is evident that, with the same amount of modified barite, increasing the amount of Poly-Q is necessary to slow down barite sedimentation and maintain the stability of the mixture.
[0239] Table 2. Stratification and Settlement Experiment Data (90℃)
[0240]
[0241] Following the same proportions, two new mixtures, numbered 3 and 4, were prepared and sealed. Each mixture was then placed in a 90°C water bath for stratification and sedimentation tests. Table 2 yields conclusions similar to those in Table 1. However, Table 2 shows that mixture 3 stratified after 72 hours and began to precipitate after 96 hours; further increases in precipitate time increased the amount of precipitate. Mixture 4 showed stratification and partial precipitation after 96 hours; further extension of precipitate time increased the amount of precipitate, but the amount was less than that of mixture 3.
[0242] Test Example 2
[0243] The hydrophobic associating polymer Poly-Q prepared in Example 3 was added at a rate of 20 wt.% and the barite modified by the modified polymer Poly-G prepared in Example 6 was added at a rate of 15 wt.%, and the mixture was thoroughly mixed with deionized water to form a mixture labeled as 5. The hydrophobic associating polymer Poly-Q prepared in Example 3 was added at a rate of 40 wt.% and the barite modified by the modified polymer Poly-G prepared in Example 6 was added at a rate of 45 wt.%, and the mixture was thoroughly mixed with deionized water to form a mixture labeled as 6. The density of the mixtures was tested.
[0244] Experimental results show that the density of the mixture formed by 20 wt.% hydrophobic associating polymer Poly-Q and 15 wt.% modified barite is 1.2 g / cm³. 3 The mixture formed by 40 wt.% of the hydrophobic associating polymer Poly-Q and 45 wt.% of modified barite has a density of 2.0 g / cm³. 3 .
[0245] Test Example 3
[0246] Sodium persulfate was added to mixtures 5 and 6, and the mixture was heated and stirred at 120°C (600 rpm) for 1 hour to disrupt the molecular structures of Poly-Q and Poly-G. Then, at room temperature (27°C), mixtures 5 and 6 were divided into three equal portions, and white oil was added to each portion at volume ratios of 3:7, 1:1, and 7:3, respectively, and the mixtures were stirred at 500 rpm to form emulsions. The resulting emulsions were numbered 7, 8, 9 and 10, 11, 12, respectively. The demulsification voltage of these emulsions was tested. The experimental results are shown in Table 3.
[0247] Table 3 Results of emulsion stability experiments
[0248]
[0249] Note: The unit of demulsification voltage is V.
[0250] As shown in Table 3, the high demulsification voltage indicates that the formed emulsion is relatively stable. When the molecular structures of Poly-Q and Poly-G are disrupted, the quaternary ammonium salt, sulfonate, and carboxylate groups within their respective molecular structures allow the broken molecular chains containing these groups to fully emulsify the mixed oil phase, forming a stable emulsion.
[0251] Test Example 4
[0252] The surface tension of the emulsion in Test Example 3 was tested, and the experimental results are shown in Table 4.
[0253] Table 4. Experimental data for surface tension testing
[0254]
[0255]
[0256] As shown in Table 4, when the molecular structures of Poly-Q and Poly-G are disrupted, the broken molecular chains containing quaternary ammonium salt, sulfonate, and carboxylate groups can fully emulsify the mixed oil phase, forming a stable emulsion.
[0257] As the proportion of oil phase mixed in increases, the surface tension of the resulting emulsion also increases. However, due to the disruption of the molecular structures of Poly-Q and Poly-G, a large number of broken molecular chains or molecular groups containing quaternary ammonium salt structures, sulfonate structures, and carboxylate structures are distributed in the emulsion.
[0258] These molecular chains or groups allow the aqueous and oil phases to form relatively stable emulsions. It is also because of the presence of these molecular chains or groups that the emulsions exhibit low surface tension.
[0259] This facilitates the on-site treatment of the completion fluid, making it easier to be pumped to the surface along with the fluids in the formation.
[0260] Test Example 5
[0261] The hydrophobic associating polymer Poly-Q prepared in Example 3 was added at a rate of 20 wt.% and the barite modified by the modified polymer Poly-G prepared in Example 6 was added at a rate of 15 wt.%, and the mixture was thoroughly mixed with deionized water to form a mixture, which was numbered 13; the hydrophobic associating polymer Poly-Q prepared in Example 3 was added at a rate of 40 wt.% and the barite modified by the modified polymer Poly-G prepared in Example 6 was added at a rate of 45 wt.%, and the mixture was thoroughly mixed with deionized water to form a mixture, which was numbered 14. The sealing properties of the mixtures were tested.
[0262] Six core samples were collected, consisting of mudstone, sandstone-mudstone interbedded layers, and sandstone, and placed in core holders. Mixtures numbered 13 and 14 were injected using a constant flow pump at a rate of 3 ml / min. The pressure gauge readings at the liquid inflow ports were observed to determine the sealing effect. The experimental results are shown in Table 5.
[0263] Table 5. Well Completion Fluid Sealing Performance Test
[0264]
[0265]
[0266] As shown in Table 5, with the increase of the completion fluid density, cores with low permeability have the best plugging effect; cores with high permeability have a poorer plugging effect. However, they still have a good plugging effect.
[0267] Test Example 6
[0268] The hydrophobic associating polymer Poly-Q prepared in Example 3 and the modified barite prepared in Example 6 with polymer Poly-G were thoroughly mixed with deionized water to form a mixture with a density of 1.5 g / cm³. 3 The mixture is numbered 15.
[0269] Simulated old drilling fluid formulation: 5 wt.% bentonite + 2 wt.% Na₂CO₃ + polyacrylamide (weight average molecular weight 2000 g / mol) + barite + deionized water. Prepare solutions with a density of 1.5 g / cm³. 3 .
[0270] Simulate the existing completion fluid formulation 1: 5 wt.% bentonite + polyacrylamide (weight average molecular weight 2000 g / mol) + barite + inorganic salt + deionized water. Prepare fluids with a density of 1.5 g / cm³. 3 .
[0271] Simulate existing completion fluid formulation 2: 5 wt.% bentonite + polyacrylamide (weight average molecular weight 2000 g / mol) + barite + organic salts + deionized water. Prepare fluids with a density of 1.5 g / cm³. 3 .
[0272] N80 steel sheets were placed in the above liquid and corroded in a 90℃ water bath for 2 hours. The experimental results are shown in Table 6.
[0273] Table 6 Corrosion Test Data
[0274]
[0275] Table 6 shows that completion fluid formulas 2 and 1 are more corrosive, while the drilling fluid is slightly less corrosive. Because the old drilling fluid uses larger barite particles, a significant amount of barite precipitate was found at the bottom of the steel sheet after the experiment; in addition, many barite particles also adhered to the surface of the steel sheet. The barite particles formed bridging, and in the ionized atmosphere created by Na2CO3 ionization, they formed a galvanic cell structure with the steel sheet, promoting corrosion of the steel sheet in the old drilling fluid. Therefore, it can be seen that using old drilling fluid not only easily buries and jams the completion string, but also causes corrosion to the completion string.
[0276] Completion fluid formula 1 and completion fluid formula 2 contain inorganic and organic salts. When these salts ionize in deionized water, they are evenly distributed throughout the water. At this time, the steel sheet is placed in the surrounding high-concentration electrolyte solution, which also forms a galvanic cell structure and accelerates the corrosion of the steel sheet.
[0277] The mixed fluid and old drilling fluid No. 15 are less corrosive than completion fluid formulations 1 and 2 because they are encapsulated by polymer-formed gels and are not surrounded by high concentrations of electrolytes such as salts.
[0278] In mixture 15, the modified barite was suspended in the Poly-Q polymer atmosphere without any sedimentation. The steel sheet was well encapsulated in the Poly-Q polymer atmosphere of the completion fluid, resulting in a relatively low corrosion rate.
[0279] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention, including combinations of various technical features in any other suitable manner, should also be considered as the content disclosed in the present invention and should be included within the protection scope of the present invention.
Claims
1. A well completion fluid, characterized in that, It is composed of a hydrophobic associating polymer Poly-Q, modified barite, and water. The hydrophobic associating polymer Poly-Q is prepared by polymerization of monomers A, B, C, D, and E. in, The chemical structural formula of monomer A is: Where n = 1 to 5; The chemical structural formula of monomer B is: Where R1 is ; The chemical structural formula of monomer C is: ; The chemical structural formula of monomer D is: ; The chemical structural formula of monomer E is: ; The molar ratio of monomers A, B, C, D, and E is (0.2~1):(0.3~1):(0.5~1):(0.2~1):(0.3~1); The hydrophobic associative polymer Poly-Q has a weight-average molecular weight of 15 million to 20 million g / mol. The modified barite is prepared by grafting a modified polymer, Poly-G, onto the surface of barite. The modified polymer, Poly-G, is a copolymer formed by a polymerization reaction and contains monomers F, G, H, and K. The monomer F is , The monomer G is , The monomer H is , The monomer K is ; The molar ratio of monomers F, G, H and K is (0:3~1):(0.5~1):(0.5~1):(0.2~1); the weight-average molecular weight of the modified polymer Poly-G is 10 million to 20 million g / mol.
2. The completion fluid according to claim 1, characterized in that, The hydrophobic associative polymer Poly-Q has a molecular weight distribution of 1.1 to 1.3; the modified polymer Poly-G has a molecular weight distribution of 1.1 to 1.
3.
3. The well completion fluid according to claim 1, characterized in that, The barite has a particle size of 200~600nm.
4. The well completion fluid according to claim 1, characterized in that, The hydrophobic associative polymer Poly-Q accounts for 10 wt.% to 40 wt.%, the modified barite accounts for 10 wt.% to 45 wt.%, and the remainder is water.
5. The well completion fluid according to claim 1, characterized in that, After the completion fluid is broken down by oxidized salts, the broken-down fluid can form a relatively stable emulsion with the oil phase.
6. A method for preparing the well completion fluid according to any one of claims 1-5, characterized in that, The preparation of the hydrophobic associating polymer Poly-Q includes the following steps: S1. Emulsifier, alkali metal carbonate and / or alkali metal bicarbonate and water are stirred at a high speed of 500~600 r / min for 20min~30min to obtain emulsifier mixture; The ratio of the amount of emulsifier, the amount of alkali metal carbonate and / or alkali metal bicarbonate to the volume of water is (0.4~0.6):(0.2~0.5):
100. S2. Add monomers A, B, C, D and E in a molar ratio of (0.2~1):(0.3~1):(0.5~1):(0.2~1):(0.3~1) to the emulsifier mixture dropwise. During this process, inert gas is introduced at a rate of 0.3~0.5 L / min for protection, and the emulsion is stirred with a shear emulsifying stirrer at a shear rate of 300~400 r / min until it is uniformly mixed. The ratio of the total amount of substance of monomers A, B, C, D and E to the volume of water in step S1 is (3~5):
100. S3. Transfer the emulsion reaction mixture obtained in step S2 to a reaction vessel and introduce inert gas at a rate of 0.3~0.5L / min for protection. Under a stirring speed of 200~300r / min, heat the emulsion to 45~50℃ at a heating rate of 1℃ / min and keep it at that temperature for 5~8min. Then add 1 / 4~1 / 3 of the weight of initiator. Continue stirring at a speed of 200-300 r / min, and introduce inert gas at a rate of 0.3-0.5 L / min and stir for 15-20 min. Then, heat the emulsion to 55-60°C at a heating rate of 1°C / min and hold it at that temperature for 5-8 min. Finally, add the remaining weight of initiator. Stir at a speed of 200~300 r / min, and introduce inert gas at a rate of 0.3~0.5 L / min and stir for 15~20 min. Then, heat to 70℃ at a heating rate of 1℃ / min, stop introducing inert gas, close the reaction vessel, and keep the reaction at this temperature for 8 h. S4. Cool the mixed product obtained in step S3 to 40~45℃, add alkali metal carbonate or alkali metal bicarbonate to adjust its pH value to neutral, and further cool to 25~30℃. After washing with anhydrous ethanol and drying, the hydrophobic associative polymer Poly-Q is obtained.
7. The method according to claim 6, characterized in that, The emulsifier is at least one of Span60, polysorbate-85, OS-15, sodium dodecyl sulfonate, and sodium dodecyl diphenyl ether disulfonate; the alkali metal carbonate includes sodium carbonate, potassium carbonate, or a mixture thereof; the alkali metal bicarbonate includes sodium bicarbonate, potassium bicarbonate, or a mixture thereof.
8. The method according to claim 6, characterized in that, The initiator is potassium persulfate or ammonium persulfate, wherein the ratio of the amount of initiator to the volume of water in step S1 is 0.03~0.05:
100.
9. The method according to claim 6, characterized in that, The method for preparing the modified polymer Poly-G includes the following steps: Step 1: Mix the emulsifier and water at a high speed of 600~800r / min for 20min~30min to obtain an emulsifier mixture; The ratio of the amount of emulsifier to the volume of water is (0.6~0.8):
100. Step 2: Add monomers F, G, H and K in a molar ratio of (0:3~1):(0.5~1):(0.5~1):(0.2~1) dropwise to the emulsifier mixture. During this process, inert gas is introduced at a rate of 0.6~0.8 L / min for protection, and a shear emulsification stirrer is used to stir the emulsion at a shear rate of 500~600 r / min until the mixture is uniform. The ratio of the total amount of substance of monomers F, G, H and K to the volume of water in Step 1 is (5~8):
100. Step 3: Transfer the emulsion obtained in Step 2 to a reaction vessel and introduce inert gas at a rate of 0.6~0.8L / min for protection. Under a stirring speed of 350~500r / min, heat the emulsion to 50~60℃ at a heating rate of 1℃ / min and hold it at that temperature for 5~8min. Then add 1 / 4~1 / 3 of the weight of initiator. Continue stirring at a speed of 350-500 r / min, and introduce inert gas at a rate of 0.6-0.8 L / min and stir for 15-20 min. Then, heat the emulsion to 65-70°C at a heating rate of 1°C / min and hold it at that temperature for 5-8 min. Finally, add the remaining weight of initiator. Continue stirring at a speed of 350-500 r / min and introduce inert gas at a rate of 0.6-0.8 L / min for 15-20 min. Then, heat the emulsion to 75°C at a heating rate of 1°C / min and keep it at that temperature. Stop introducing inert gas, close the reaction vessel, and keep the reaction at that temperature for 4 h. Stop the reaction and continue stirring at a rate of 200 r / min. After the reaction liquid cools down naturally to 30~35℃, reduce the stirring speed to 100 r / min and continue cooling to room temperature (25±2℃). Stop stirring to obtain an emulsion containing the modified polymer Poly-G. The ratio of the amount of initiator to the volume of water in step S1 is 0.06~0.08:100; wherein the initiator is potassium persulfate or ammonium persulfate. Step 4: The emulsion obtained in Step 3 is washed and dried with anhydrous ethanol at room temperature, and the resulting solid is the modified polymer Poly-G.
10. The method according to claim 9, characterized in that, The emulsifier is at least one of OP-4, OP-50, sodium decyl sulfate, and sodium tetradecyl sulfate.
11. The application of the well completion fluid according to any one of claims 1-5 in oil and gas field exploration and development.
Citation Information
Patent Citations
Ultrahigh-temperature-resistant and complex-salt-resistant amphoteric ion hydrophobic association polymer filter loss reducer and preparation method thereof
CN108715624A
Copolymer for modification, novel modified barite weighting material, preparation method and application of novel modified barite weighting material, and drilling fluid containing modified barite
CN114349900A